ISOLATION AND IDENTIFICATION OF LACTIC ACID BACTERIA FROM GAMBUT TAPE - Hanasia, Hanasia; Martani, Natalia Sri; Turnip, Oktaviani Naulita; Putri Welmart, Devina Vania; Puspita Sari, Dewi Marta (Meditory : The Journal of Medical Laboratory, 2025)
Background: Lactic acid bacteria (LAB) are Gram-positive bacteria with probiotic properties, contributing to digestive health by balancing gut microflora. These bacteria are commonly found in fermented products, including gambut tape, a traditional Indonesian fermented food from Kalimantan. Gambut tape is known for its distinctive green color derived from katuk and pandan leaves.Objective:  This study aims to isolate and identify LAB from the gambut tape. Methods: LAB were isolated using Man, Rogosa, and Sharpe (MRS) agar and incubated at 37°C for 24 hours. Identification was performed through biochemical tests, including Gram staining, catalase, citrate, H2S, motility, indole, carbohydrate fermentation, methyl red, and Voges-Proskauer tests.Results:  Three isolates were obtained, exhibiting similar morphological features: milky white color, round shape, intact edges, convex elevation, and smooth surface. Biochemical results suggested that the isolates are identical to Lactococcus lactis, Lactobacillus plantarum, and Lactobacillus fermentum.Conclusions: The LAB isolated from the gambut tape shows potential as an antibacterial agent for disease prevention. Further research is needed to evaluate their antibacterial activity and characterize bacteriocins produced by these LAB.